System architecture patterns a domain-based proposition - Ramasubramaniam, K.; Annamalai, G.; Krishna, Aneesh (2015)
© 2015 IEEE. This paper proposes system architecture patterns (similar to software architecture patterns) and also describes the practical experiences of designing the system architecture of a 'combo' product (eg DVD player/recorder combined with TV, Set top Box functionality with Android application ecosystem etc.) based on two separate heterogeneous system architectures. We have proposed five system architecture patterns (currently) via which such combo system architectures can be derived. The first is a simple combination with minimal modifications pattern (SiCo). The second is a combination with modifications (CoMo). The third is a central controller pattern (CC). The fourth is a Redesign and Re-architect pattern (RDRA). The fifth is an Independent Standalone Subsystems (ISS) pattern. The details of each pattern are explained together with the scenarios where they can be used. Some examples for each scenario are also highlighted. Some of our practical experiences in the industry are also highlighted.